Stereochemical Investigations of Diastereomeric N-[2-(Aryl)-5-methyl-4-oxo-1, 3-thiazolidine-3-yl]-pyridine-3-carboxamides by Nuclear Magnetic Resonance Spectroscopy (1D and 2D). (31st December 2015) - Demir-Ordu, Öznur; Demir-Dündar, Hale; Ozkirimli, Sumru
Abstract : Some new N -[2-(aryl)-5-methyl-4-oxo-1, 3-thiazolidine-3-yl]-pyridine-3-carboxamides were synthesized and their structures were investigated by IR, NMR ( 1 H, 13 C, and 2D), and mass spectra. The presence of C-2 and C-5 stereogenic centers on the thiazolidinone ring resulted in diastereoisomeric pairs. The configurations of two stereogenic centers were assigned based upon 1 H NMR analysis of coupling constants and 2D nuclear overhauser enhancement spectroscopy (NOESY) experiment. Resolution of the diastereoisomers was performed by high performance liquid chromatography (HPLC) using a chiral stationary phase.